The effect of hybridization on mechanical properties of woven kenaf fiber reinforced polyoxymethylene composite - Dan-Mallam, Y. (John Wiley and Sons Inc, 2014)
The challenges of using natural fibers in polymer composites include high moisture uptake and poor interfacial bonding with thermoplastic matrix. In this study, the effect of hybridization was investigated to address the challenges of high moisture uptake and balanced mechanical properties in natural fiber reinforced polymer composites. Polyethylene terephthalate fiber (PET) was used in woven kenaf reinforced POM due to its hydrophobic characteristics. The results of tensile test showed that the tensile strength of the interwoven POM/kenaf/PET hybrid composite when tested along kenaf fiber direction, increased from 72 to 85 MPa due to increase in fiber content. Similarly, the tensile strength of the interwoven POM/kenaf/PET hybrid composite increased from 67 to 75 MPa. However, the flexural strength of the interwoven POM/kenaf/PET hybrid composite dropped from 160.1 to 104.9 MPa while that of woven POM/kenaf composite dropped from 191.4 to 90.3 MPa. The interwoven hybrid composite also showed significant improvement in impact strength compared to the woven POM/kenaf composite. The water absorption of the woven POM/kenaf composite dropped by approximately 30 due to hybridization with PET fiber. The results confirmed that hybridization with PET fiber significantly improved the tensile and impact properties of the woven composite and increased its resistance to moisture uptake. Â© 2014 Society of Plastics Engineers.